SINTESIS DAN KARAKTERISASI MOLECULARLY IMPRINTED POLYMERS MENGGUNAKAN METIL METAKRILAT DAN ETILEN GLIKOL DIMETAKRILAT SEBAGAI ADSORBEN DI-(2-ETILHEKSIL) FTALAT (SYNTHESIS AND CHARACTERIZATION OF MOLECULARLY IMPRINTED POLYMERS USING METHYL METHACRYLATE AND ETHYLENE GLYCOL DIMETACRILATE AS ADSORBENT DI-(2-ETILHEKSIL) PHTHALATE) - Risna Jupri; St Fauziah; Paulina Taba (Indonesian Journal of Pure and Applied Chemistry, 2022)
Molecularly Imprinted Polymer (MIP) is an intelligent synthetic material because it has the ability to selectively recognize target molecules. This study aims to synthesize, characterize and analyze the performance of MIP. MIP material was synthesized using di-(2-Ethylhexyl) phthalate (DEHP) as a template molecule, methyl methacrylate (MMA) monomer combined with ethylene glycol dimethacrylate (EGDMA) as a crosslinker by precipitation polymerization method. MIP materials were characterized by SEM-EDS instrument, FTIR spectrometer, SAA instrument, and UV-Vis spectrophotometer. The test variables for the adsorption ability of MIP material on DEHP compounds were time and concentration. The results showed that the synthesized MIP was in the form of a coarse white solid with a stiff texture. Characterization with the EDS instrument showed a decrease in the mass percent of C and percent of C atoms which indicated the formation of MIP_DEHP_MMA-co-EGDMA(TE) and the surface morphology characterized by the SEM instrument was composed of small grains that tend to be uniform and have pores. The bonds that affect the formation of polymers characterized by FTIR were –C=C, –C=O, and –CO. Characterization with the SAA instrument was 142,2770 m2/g, the total pore volume was 0,2616 cm3/g and the average pore radius was 7.3562 nm, indicating mesoporous material. The optimum time for adsorption of MIP_DEHP_MMA-co-EGDMA(TE) to DEHP was 120 minutes. MIP_DEHP_MMA-co-EGDMA(TE) followed the pseudo-second-order kinetics model and the adsorption obeyed the Freundlich adsorption isotherm